The Acute Effects of a Percussive Massage Treatment with a Hypervolt Device on Plantar Flexor Muscles’ Range of Motion and Performance - Konrad, Andreas (J Sports Sci Med, 2020)
Handheld percussive massage treatment has gained popularity in recent years, for both therapeutic use and in sports practice. It is used with the goals of increasing flexibility and performance, but also to accelerate recovery. However, until now, there has been no scientific evidence, which proves such effects. Therefore, the purpose of this study was to investigate the effects of a 5-min percussion treatment of the calf muscles on range of motion (ROM) and maximum voluntary contraction (MVC) torque of the plantar flexor muscles. Sixteen healthy male volunteers (mean ± SD; 27.2 ± 4.2 years, 1.79 ± 0.05 m, 79.4 ± 9.1 kg) were tested on two separate days with either a 5-min massage treatment of the calf muscles with a Hypervolt device or the control condition (sitting only). Before and after the treatments, dorsiflexion ROM and MVC torque of the plantar flexor muscles were measured with a dynamometer. Maximum dorsiflexion ROM increased with a large magnitude following the massage treatment by 5.4° (+18.4%; p = 0.002, d= 1.36), while there was no change in the control group. Moreover, MVC torque did not change following both the massage treatment and the control treatment. Similar to a conventional massage by a therapist, ROM can be increased by a handheld percussive massage treatment without having an effect on muscle strength.